2019
DOI: 10.7150/thno.35665
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Mechanics-Induced Fibroblast Activation through CD44-RhoA-YAP Pathway Ameliorates Crystalline Silica-Induced Silicosis

Abstract: Silicosis is pneumoconiosis of the lung, usually resulting from prolonged exposure to crystalline silica (CS). The hallmark of silicosis is excessive extracellular matrix (ECM) deposition produced by activated fibroblasts. Recent work demonstrated that excessive ECM-forming mechanical cues play an essential role in promoting fibroblast activation and perpetuating fibrotic pathologies. However, the detailed molecular mechanism still needs to be uncovered. Methods : NIH-3T3 fibroblasts we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 50 publications
1
51
0
Order By: Relevance
“…CS particulates (Min-U-Sil 5 ground silica with size distribution of 97% < 5 µm diameter, 80% < 3 µm diameter, and median diameter 1.4 µm) were purchased form the U.S. Silica Company (Frederick, MD, USA). The pretreatment of CS and the establishment of silicosis animal models were performed as previously described [25,26]. The schematic representation for the in vivo treatment schedule is presented in Figure S1.…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…CS particulates (Min-U-Sil 5 ground silica with size distribution of 97% < 5 µm diameter, 80% < 3 µm diameter, and median diameter 1.4 µm) were purchased form the U.S. Silica Company (Frederick, MD, USA). The pretreatment of CS and the establishment of silicosis animal models were performed as previously described [25,26]. The schematic representation for the in vivo treatment schedule is presented in Figure S1.…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…YAP has been shown to be involved in the regulation of the TGF‐β1 signalling pathway, potentially through directly binding Smad2/3 to enhance renal fibroblast activation 32 . Moreover, overexpression of YAP has been demonstrated in lung, renal and liver fibrosis 33‐35 . It is worth noting that YAP has been linked to the TGF‐β1/Smad pathway in mouse models of kidney fibrosis 36 .…”
Section: Discussionmentioning
confidence: 99%
“…32 Moreover, overexpression of YAP has been demonstrated in lung, renal and liver fibrosis. [33][34][35] It is worth noting that YAP has been linked to the TGF-β1/Smad pathway in mouse models of kidney fibrosis. 36 Consistent with previous studies, our findings also indicated that YAP plays an important role in TGF-β1mediated retinal fibrosis.…”
Section: F I G U R Ementioning
confidence: 99%
“…To observe the anti-fibrotic effect of miR-155-5p, specific pathogen-free male C57BL/6 mice weighting 15 ± 3 g at 8 weeks of age were purchased from Vital River Laboratory Animal Technology. Animals were randomly divided into three groups as follows (n = 6): agonist miRNA negative control (agomiR-NC), 0.05 mL of 0.9% saline containing 5 nmol ago-NC; silica plus agomiR-NC, 0.05 mL of 0.9% saline containing 5 nmol ago-NC plus 2.5 mg SiO 2 ; silica plus agomiR-155-5p group, 0.05 mL of 0.9% saline containing 5 nmol agomiR-155-5p plus 2.5 mg SiO 2 administered via trachea instillation 23 , 24 . Subsequently, 2.5 nmol of ago-NC or agomiR-155-5P was injected via the tail vein at 1 week after silica treatment.…”
Section: Methodsmentioning
confidence: 99%